The immune function of prophenoloxidase from red swamp crayfish (Procambarus clarkii) in response to bacterial infection. Issue 92 (September 2019) - Qin, Zhendong; Sarath Babu, V.; Lin, Hanzuo; Dai, Yunjia; Kou, Hongyan; Chen, Liehuan; Li, Jun; Zhao, Lijuan; Lin, Li
Abstract: Prophenoloxidase (proPO) is the zymogen form of phenoloxidase (PO), a key enzyme in melanization cascade that has been co-opted in invertebrate immune reactions. There have been reported that proPO plays many essential roles in the crustacean immune system. However, little is known about the function of proPO from red swamp crayfish ( Procambarus clarkii ) which is an important cultured species worldwide. Here, we cloned and expressed proPO gene from red swamp crayfish ( Pc proPO). Subsequently, specific antibody against Pc proPO was generated. The immune function of Pc proPO was further characterized in vitro and in vivo. The results showed that the expression of Pc proPO mRNA could be significantly up-regulated during the challenge of Gram-positive-negative ( Vibrio parahaemolyticus ) and Gram-positive-positive bacterial ( Staphylococcus aureus ). Furthermore, the purified recombinant Pc proPO protein had a strong affinity binding to both bacteria and polysaccharides. In vivo knockdown of Pc proPO could significantly reduce the crayfish bacterial clearance ability, resulting in the higher mortality of the crayfish during V. parahaemolyticus infection . In addition, in vitro knockdown of Pc proPO in the hemocytes significantly reduced the phenoloxidase (PO) activity and the bacterial clearance ability, indicating that Pc proPO might involve in hemocyte-mediated melanization. Our results will shed a new light on the immune function of Pc proPO in the crayfish. Highlights: Pc proPO of red swamp crayfish could bind to both Gram positive and negative bacteria. In vivo knockdown of Pc proPO could decrease the capacity of bacterial clearance and survival rate of the crayfish. In vitro knockdown of Pc proPO could reduce PO activity, bacterial clearance and melanization ability in hemocytes . Pc proPO has a vital role in antibacterial innate immune response.